New Insight into the Confinement Effect of Microporous Carbon in Li/Se Battery Chemistry: A Cathode with Enhanced Conductivity. Issue 17 (29th March 2020) - Wang, Xiwen; Tan, Yuqing; Liu, Zhixiao; Fan, Yuqin; Li, Mingnan; Younus, Hussein A.; Duan, Junfei; Deng, Huiqiu; Zhang, Shiguo
Abstract: Embedding the fragmented selenium into the micropores of carbon host has been regarded as an effective strategy to change the Li–Se chemistry by a solid–solid mechanism, thereby enabling an excellent cycling stability in Li–Se batteries using carbonate electrolyte. However, the effect of spatial confinement by micropores in the electrochemical behavior of carbon/selenium materials remains ambiguous. A comparative study of using both microporous (MiC) and mesoporous carbons (MeC) with narrow pore size distribution as selenium hosts is herein reported. Systematic investigations reveal that the high Se utilization rate and better electrode kinetics of MiC/Se cathode than MeC/Se cathode may originate from both its improved Li+ and electronic conductivities. The small pore size (<1.35 nm) of the carbon matrices not only facilitates the formation of a compact and robust solid‐electrolyte interface (SEI) with low interfacial resistance on cathode, but also alters the insulating nature of Li2 Se due to the emergence of itinerant electrons. By comparing the electrochemical behavior of MiC/Se cathode and the matching relationship between the diameter of pores and the dimension of solvent molecules in carbonate, ether, and solvate ionic liquid electrolyte, the key role of SEI film in the operation of C/Se cathode by quasi‐solid‐solid mechanism is also highlighted. Abstract : For microporous carbon/Se cathode in carbonate electrolyte, micropores facilitate the formation of thin LiF‐rich solid electrolyte interphase on the C/Se cathode, allowing fast Li + conduction. The nanoconfinement of micropores can generate the itinerant electrons and alter the insulating nature of Li2 Se.